Length of hospital stay and dementia: A systematic review of observational studies. (27th September 2018) - Möllers, Tobias; Stocker, Hannah; Wei, Wenjia; Perna, Laura; Brenner, Hermann
Abstract : Objective: Hospitalizations of people with dementia (PWD) are often accompanied by complications or functional loss and can lead to adverse outcomes. Unsystematic findings suggest an influence of comorbidities on the extent of differences in the length of hospital stay (LOS). This systematic review aimed to identify and evaluate all studies reporting LOS in PWD as compared to PwoD in general hospitals. Methods: A systematic review of observational studies using PubMed and ISI Web of Knowledge. Inclusion criteria comprised original studies written in English or German, assessment of diagnosis of dementia, measurement of LOS, and comparison of people with and without dementia. Results: Fifty‐two of 60 studies reported a longer hospitalization time for PWD compared to PwoD. The extent of the difference in LOS varied between and within countries as well as by type of primary morbidity (eg, injuries, cardiovascular diseases). The range of the LOS difference for studies without restriction to a primary morbidity was −2 to +22 days after matching or adjustment for a variable number and selection of potentially relevant covariates. For studies with injuries/fractures/medical procedures and infectious/vascular disease as the primary morbidity, the range was −2.9 to +12.4 and −11.2 to +21.8 days, respectively. Conclusions: The majority of studies reported a longer hospitalization of PWD compared to PwoD. Length of hospital stay seems to be influenced by a variety of medical, social, organizational factors, including reasons for hospital admission, whose role should be explored in detail in further research.